2013
DOI: 10.1007/s13595-013-0268-x
|View full text |Cite
|
Sign up to set email alerts
|

Veneer grades, recoveries, and values from 5-year-old eucalypt clones

Abstract: & Context Processing young, small eucalypt logs into veneer is a burgeoning industry across southern China. However, plantations supplying these logs were mostly established for pulpwood; little information is available on variation and selection among commercial eucalypt clones/varieties in regards to suitability for veneer production. & Methods Tree growth and log form were assessed on 11 eucalypt clones from a 5-year-old trial in southern China. Logs from these were rotary peeled for veneer; recovery percen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 2 publications
(2 reference statements)
3
18
2
Order By: Relevance
“…These values are quite low compared with this study, which could possibly be attributed to the application of traditional technologies, which produce larger diameter peeler cores and failed peeling due to spindle grip problems (e.g., core splitting). In a study using spindleless lathe technology in China, Luo et al (2013) reported an average green veneer recovery (defined similarly to gross veneer recovery in this study) of 44% (ranging from 28% to 51%) for 11 different five-year-old eucalypt clones. The comparatively low green veneer recovery observed is likely attributable to a lower average small-end diameter of the billets (112 mm).…”
Section: Resultssupporting
confidence: 52%
See 1 more Smart Citation
“…These values are quite low compared with this study, which could possibly be attributed to the application of traditional technologies, which produce larger diameter peeler cores and failed peeling due to spindle grip problems (e.g., core splitting). In a study using spindleless lathe technology in China, Luo et al (2013) reported an average green veneer recovery (defined similarly to gross veneer recovery in this study) of 44% (ranging from 28% to 51%) for 11 different five-year-old eucalypt clones. The comparatively low green veneer recovery observed is likely attributable to a lower average small-end diameter of the billets (112 mm).…”
Section: Resultssupporting
confidence: 52%
“…According to Arnold et al (2013), there are more than 5,000 small-scale veneer mills in China dedicated to the processing of young, smalldiameter eucalypt logs. However, there are few publications providing detailed information on the veneer quality and recovery from spindleless lathe technology (e.g., Luo et al 2013). To date, there are no published recovery data (including product grade recovery) for the use of this technology in the processing of Australia's plantation resources, which involve different species and climates from those in Asian countries.…”
Section: Introductionmentioning
confidence: 99%
“…These plantation trees present many advantages, such as fast growth and straight stem form, which make them suitable for plywood production. Production of plywood in China has increased rapidly over the last 20 years from 2.1 million m 3 in 1993 to more than 50 million m 3 in 2010 (Luo et al 2013). Such high productivity makes it necessary to evaluate the quality of veneer.…”
Section: Introductionmentioning
confidence: 99%
“…Different veneer grading methods also help explain the variation. Luo et al (2013) reported an average green veneer recovery (defined similarly to gross veneer recovery in this study) of 44% (ranging from 28% to 51%) for 11 different five-year-old eucalypt clones in China. While adopting spindleless lathe technology, similar to this study, the comparatively low green veneer recovery observed is likely attributable to a lower average small-end diameter of the billets (112 mm).…”
Section: Visual Gradingmentioning
confidence: 55%